(untitled) (AmeriQuests, 2011)
The production of positive national images is currently high on the political agenda in Brazil. While Brazil’s economic growth and increasing importance in the international arena, both politically and economically, are undeniable, it seems that there is quite a lot of work to do in the social–psychological sphere to keep up with the economic advances. Our research has shown that while Brazil’s official discourse and Brazilians’ individual discourses are tendentious and tend to create an image of Brazil and of Brazilians as more receptive than other nations and indeed as almost xenophile, at the same time people hold strongly xenophobic views but tend to deny it and escape behind the normative discourse of receptivity. We analyse collected discourses and present various forms of denial of xenophobia in Brazil via a qualitative study conducted in a university setting in São Paulo.